The Functions of Economy News Taken Port in Newspapers to Social Development (Example of the Dunya Newspaper) - Barut, Basri; Demir, Umit (Istanbul Univ, 2005)
The newspaper have functions, corresponding to social development, to give news and to inform and also educating, warning, conducing culture evolution, socializing, motivating, preparing a discussion atmosphere, integrating and transferrnig the problems to the community. Development is not only related with the growth of the economy, at the same little it needs the social and cultural change. From beginning of the eighties, with expansion of the Turkey's economy, activation of capital markets, liberating rate of interest and currency; the requirement of economical news caused primarily increase of economy news pages that emanated economy journals and reviews. At taking new to investment decisions and consolidation the existing economy structure, economy press had important contributions and it became an effective partner of social development. With the thought of economical development would bring social development, examining the subject on the pivot of the economic development, the functions of the economy news on social development is researched and manifested with literature scanning method. A field survey is performed for testing the theoretical frame, which as composed with the acquired data. Simple random sampling method has been used and 100 Dunya Newspaper subscriber company has been chosen in Elazig and has been subjected to as questionnnaire. Acquired date has analyzed with SPSS version 9.05 on computer. It has been reached to important evidences in this study with the assist of this analyses about the field survey.
Keywords: Economy News; Medina Economic Functions; Media's Social functions; Social Development; Regional Development